Locating the "Liberal" in Neoliberal A Response to James Crossley - Boer, Roland 1961- (2014)
A critical review of James Crossley's Jesus in an Age of Neoliberalism
Keywords: Classical Economic; Jesus; Liberalism; Neoclassical Economics; Neoliberalism